Protospacer modification improves base editing of a canonical splice site variant and recovery of CFTR function in human airway epithelial cells - Anya T. Joynt; Erin W. Kavanagh; Gregory A. Newby; Shakela Mitchell; Alice C. Eastman; Kathleen C. Paul; Alyssa D. Bowling; Derek L. Osorio; Christian A. Merlo; Shivani U. Patel; Karen S. Raraigh; David R. Liu; et al. (Elsevier, 2023)
Canonical splice site variants affecting the 5' GT and 3' AG nucleotides of introns result in severe missplicing and account for about 10% of disease-causing genomic alterations. Treatment of such variants has proven challenging due to the unstable mRNA or protein isoforms that typically result from disruption of these sites. Here, we investigate CRISPR-Cas9-mediated adenine base editing for such variants in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. We validate a CFTR expression minigene (EMG) system for testing base editing designs for two different targets. We then use the EMG system to test non-standard single-guide RNAs with either shortened or lengthened protospacers to correct the most common cystic fibrosis-causing variant in individuals of African descent (c.2988+1G>A). Varying the spacer region length allowed placement of the editing window in a more efficient context and enabled use of alternate protospacer adjacent motifs. Using these modifications, we restored clinically significant levels of CFTR function to human airway epithelial cells from two donors bearing the c.2988+1G>A variant.